The role of conservation soil management on soil and water protection at different spatial scales - Cooper, Sophie E. (Cranfield University, 2006)
Agriculture has a direct impact on the soil environment, altering soil properties, surface characteristics and erosion risk. This has led to a move away from conventional tillage to the adoption of conservation practices, aiming to minimise soil disturbance and reduce erosion. The effectiveness of this has been shown in studies from the USA, but equivalent research in Europe is limited. The present study investigated losses of soil, water, nutrients and carbon from different tillage regimes. Two UK sites were used – Loddington (Leicestershire, on heavy clay) and Tivington (Somerset on sandy clay loam). Three cultivations were applied - conventional (deep, inversion ploughing), and two forms of conservation tillage - SOWAP (non-inversion, shallow tillage), and Farmer Preference (non-inversion, deep tillage). Treatment effects were investigated at three spatial scales, ranging from field based erosion plots (0.05 ha), to micro-plots (1.5 m2), to soil aggregate tests. Results from 2004 to 2006 showed that adoption of conservation tillage did not consistently reduce losses of soil, water, nutrient and carbon, due to high temporal variability. Notable differences were found between sites. Runoff coefficients ranged from 0.39-0.46% at Loddington, and 2.43-3.82% at Tivington. Soil losses at Loddington were below 2 t ha-1 y-1, but higher at Tivington (3.47 t ha-1 y-1). Conservation tillage led to notable changes in soil properties and surface characteristics, including a decrease in bulk density and increases in organic matter, micro-topography and residue cover. Absolute values of erosion from small scale investigations could not be extrapolated directly to field scale results. Relative treatment ranks gave better comparisons, although results were not consistent for all small scale methods, due to high levels of variability. Caution should be used when extrapolating between spatial scales. Further work is required to understand the links between temporal and spatial fluctuations in soil, surface and rainfall characteristics and erosion processes.